Enzyme-Linked Immunosorbent Assay Using Recombinant OspC and the Internal 14-kDa Flagellin Fragment for Serodiagnosis of Early Lyme Disease - Rauer, Sebastian (American Society for Microbiology, 1998)
The outer surface protein C (OspC) and the internal 14-kDa flagellin fragment of strain GeHo of Borrelia burgdorferi sensu stricto were expressed as recombinant proteins in Escherichia coli and were purified for use in an immunoglobulin M (IgM) enzyme-linked immunosorbent assay (OspC–14-kDa antigen ELISA). No hint at disturbing protein-protein interferences, which might influence the availability of immunoreactive epitopes, was found when the recombinant antigens were combined in the ELISA. The recombinant OspC–14-kDa antigen ELISA was compared to a commercial IgM ELISA that used a detergent cell extract from Borrelia afzelii PKo as the antigen. According to the manufacturer’s information, the cell extract contains, in addition to other antigens, the following diagnostically relevant antigens: the 100-kDa (synonyms, 93- and 83-kDa antigens), 41-kDa, OspA, OspC, and 17-kDa antigens. The specificity was adjusted to 95% on the basis of data for 154 healthy controls. On testing of 104 serum samples from patients with erythema migrans (EM), the sensitivity of the recombinant ELISA (46%) for IgM antibodies was similar to that of the commercial ELISA (45%). However, when 42 serum samples from patients with polyclonal B-cell stimulation due to an Epstein-Barr virus infection were tested, false-positive reactions were significantly less frequent in the recombinant ELISA (10%) than in the whole-cell-extract ELISA (23%). OspC displays sequence heterogeneity of up to 40% according to the genomospecies. However, when the reactions of serum specimens from controls and EM patients with OspC from representative strains of B. burgdorferi sensu stricto (strain GeHo) and B. afzelii (strain PKo) were compared in an ELISA, almost no differences in specificity and sensitivity were seen. This demonstrates that the sera predominantly recognize the common epitopes of OspC tested in this study. In conclusion, we suggest that the OspC–14-kDa antigens ELISA is a suitable test for the detection of an IgM response in early Lyme disease.